The increase in cardiac output induced by a decrease in positive end-expiratory pressure reliably detects volume responsiveness: the PEEP-test study - Lai, Christopher; Shi, Rui; Beurton, Alexandra; Moretto, Francesca; Ayed, Soufia; Fage, Nicolas; Gavelli, Francesco; Pavot, Arthur; Dres, Martin; Teboul, Jean-Louis; Monnet, Xavier (Critical care (London, England), 2023)
Background In patients on mechanical ventilation, positive end-expiratory pressure (PEEP) can decrease cardiac output through a decrease in cardiac preload and/or an increase in right ventricular afterload. Increase in central blood volume by fluid administration or passive leg raising (PLR) may reverse these phenomena through an increase in cardiac preload and/or a reopening of closed lung microvessels. We hypothesized that a transient decrease in PEEP (PEEP-test) may be used as a test to detect volume responsiveness. Methods Mechanically ventilated patients with PEEP ≥ 10 cmH 2 O (“high level”) and without spontaneous breathing were prospectively included. Volume responsiveness was assessed by a positive PLR-test, defined as an increase in pulse-contour-derived cardiac index (CI) during PLR ≥ 10%. The PEEP-test consisted in reducing PEEP from the high level to 5 cmH 2 O for one minute. Pulse-contour-derived CI (PiCCO2) was monitored during PLR and the PEEP-test. Results We enrolled 64 patients among whom 31 were volume responsive. The median increase in CI during PLR was 14% (11–16%). The median PEEP at baseline was 12 (10–15) cmH 2 O and the PEEP-test resulted in a median decrease in PEEP of 7 (5–10) cmH 2 O, without difference between volume responsive and unresponsive patients. Among volume responsive patients, the PEEP-test induced a significant increase in CI of 16% (12–20%) (from 2.4 ± 0.7 to 2.9 ± 0.9 L/min/m 2 , p < 0.0001) in comparison with volume unresponsive patients. In volume unresponsive patients, PLR and the PEEP-test increased CI by 2% (1–5%) and 6% (3–8%), respectively. Volume responsiveness was predicted by an increase in CI > 8.6% during the PEEP-test with a sensitivity of 96.8% (95% confidence interval (95%CI): 83.3–99.9%) and a specificity of 84.9% (95%CI 68.1–94.9%). The area under the receiver operating characteristic curve of the PEEP-test for detecting volume responsiveness was 0.94 (95%CI 0.85–0.98) ( p < 0.0001 vs. 0.5). Spearman’s correlation coefficient between the changes in CI induced by PLR and the PEEP-test was 0.76 (95%CI 0.63–0.85, p < 0.0001). Conclusions A CI increase > 8.6% during a PEEP-test, which consists in reducing PEEP to 5 cmH 2 O, reliably detects volume responsiveness in mechanically ventilated patients with a PEEP ≥ 10 cmH 2 O. Trial registration ClinicalTrial.gov (NCT 04,023,786). Registered July 18, 2019. Ethics Committee approval CPP Est III (N° 2018-A01599-46).